Idiopathic gingival enlargement: A case report - Shah, Rajesh; Sharma, Shivalal (Journal of College of Medical Sciences-Nepal, 2015)
Idiopathic gingival fibromatosis is a relatively rare condition characterized by the proliferation of the gingival tissues resulting in masticatory, esthetics, phonetics and psychological disturbances. We present a case with generalized diffuse gingival enlargement involving the maxillary and mandibular arches extending on buccal and lingual/palatal surfaces and covering incisal/occlusal third of the tooth in the left maxillary region. Gingivectomy was carried out in all four quadrants. Periodic recalls showed maintenance of good oral hygiene and one year follow-up revealed no recurrence. JCMS Nepal. 2015;11(1): 26-28